PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS GAMIFIKASI DALAM MENGEMUKAKAN PENDAPAT SISWA SD SEBAGAI IMPLEMENTASI NILAI DEMOKRASI: KAJIAN LITERATUR - Shakira, Jihan; Zakirah, Yolanda; Adrias (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Conventional elementary school learning environments have failed to cultivate students' courage to express opinions, as a fundamental democratic value rooted in Pancasila's fourth principle. This study examines the potential of gamification-based learning media in fostering that courage as an implementation of democratic values in Pancasila Education. A qualitative descriptive literature review was conducted using ten articles (2020–2026) sourced from Google Scholar, Garuda, and accredited national journals, analyzed thematically through content analysis. Findings consistently show that gamification platforms, including Quizizz, Wordwall, and Kahoot! effectively increase students' active participation and willingness to speak up; Rahmatullah et al. (2022) recorded an N-Gain of 39.10%, Astuti et al. (2026) confirmed consistent effects across three schools at F(1, 61) = 306.242 (p < 0.001), and Mohammed et al. (2024) reported cross-cultural evidence with an effect size of 0.55 in the raising questions dimension. These findings affirm that gamification serves as a pedagogical bridge connecting democratic values from textual concepts toward authentic behavioral practice in elementary.